Enhanced photoelectrochemical activity of magnetically modified TiO2 prepared by a simple ex-situ route - KOCA, ATIF; KERKEZ KUYUMCU, ÖZGE (SPRINGER, 2022)
Modified TiO2 nanocomposites have been recognized as attractive photocatalytic materials in solar energy conversion. The aim of this study is to enhance the photoelectrochemical performance under visible light region by magnetically modified TiO2 nanocomposites (Fe3O4/TiO2 and NiFe2O4/TiO2) prepared by a simple ex-situ non-thermal route. The magnetic TiO2 nanocomposites were characterized by X-ray diffraction (XRD), UV-Vis diffuse reflectance spectra (DRS), photoluminescence spectroscopy (PL), transmission electron microscopy (TEM), vibrational scanning magnetometry (VSM), Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS). Photoelectrochemical analysis was performed; chronoamperometry and Mott-Schottky curves were obtained. Results indicated that these non-noble, low-cost photocatalysts have shown the desired features; NiFe2O4/TiO2 have a suitable band gap to harvest visible range of solar light; they have reduced electron-hole recombination; and it is magnetically separable from reaction media. The most promising nanocomposite was found as NiFe2O4/TiO2 with a maximum photocurrent density 132 mu A cm(-2). The possible mechanism accounting for the improved photoelectrochemical performance of NiFe2O4/TiO2 is proposed.
Keywords: Magnetic nanocomposite; NiFe2O4/TiO2; Photocurrent; LIGHT PHOTOCATALYTIC ACTIVITY; HYDROGEN-PRODUCTION; TITANIUM-DIOXIDE; HIGHLY EFFICIENT; THIN-FILMS; NANOCOMPOSITES; NANOPARTICLES; PERFORMANCE; WATER; HETEROJUNCTION